PELAKSANAAN SKRINING ANEMIA PADA CATIN WANITA DI PUSKESMAS TAPIN UTARA TAHUN 2021 - Yuliantie, Putri; Zulliati; Norma (LPPM Universitas Sari Mulia, 2022)
Background: The Indonesian Government's policy regarding the above is in the form of Regulation of the Minister of Health of the Republic of Indonesia Number 97 of 2014. This Regulation explains that pre-pregnancy health services are activities of women before pregnancy to prepare for a healthy, safe pregnancy and childbirth and to obtain a healthy baby. To ensure maternal health during pregnancy, promotive and preventive measures must be carried out from adolescence and before marriage. The targets of this activity are adolescents, prospective brides and grooms (catin) and/or couples of childbearing age. Specifically for female catin, one form of activity is pre- marital preparation in the form of nutritional preparation with an anemia status examination to determine their HB levels. Objective: To find out how Anemia Screening is Implemented in Female Catin at the Tapin Utara Health Center in 2021 Method: The research method used is quantitative descriptive observational which was carried out at the Tapin Utara Health Center with a population of 130 people and a total sampling technique was used. The data source used is secondary through the 2021 catin cohort register records. The analysis used is univariate. Results: The results of the study showed that 23 people (17.7%) had anemia and 107 people (82.3%) were not anemic. Conclusion: Catin without anemia are healthy catin who are ready to enter the reproductive process of pregnancy and childbirth. Keywords: Anemia, Catin, Screening